Dear Jean Pierre - Wojnarowicz, David; Hoff, James; Carr, Cynthia; Dubinsky, Allison (Brooklyn : Primary Information, 2023)
"Dear Jean Pierre collects David Wojnarowicz's transatlantic correspondence to his Parisian lover Jean Pierre Delage between 1979 and 1982. Capturing a truly foundational moment for Wojnarowicz's artistic and literary practice, these letters not only reveal his captivating personality--and its concomitant tenderness, compassion, and neuroses--but also index the development of the visual language that would go on to define him as one of the preeminent artists of his generation. Through this collection, readers are introduced to Wojnarowicz's Rimbaud series, the band 3 Teens Kill 4, the publication of his first photographs, his early friendship with Peter Hujar, his participation in the then-emerging East Village art and music scenes, and the preparations for the publication of his first book. Included with these writings are postcards, drawings, xeroxes, photographs, collages, flyers, ephemera, and contact sheets that showcase some of the artist's iconic images and work, such as the Burning House motif and Untitled (Genet, after Brassai). Beyond these milestones, the book offers a striking portrayal of Wojnarowicz as a twenty-something, detailing his day-to-day life with the type of unbridled earnestness that comes with that age and the softness of love and longing. This disarming tenderness provides a picture of a young man just beginning to find his voice in the world and the love he has found in it. Although the two exchanged letters in equal measure, Delage's correspondences have largely been lost, leaving us with only a revelatory glimpse into the internal world of Wojnarowicz during what turned out to be his formative years."
Edition of 4000.
kunstcatalogus
Keywords: Wojnarowicz, David